Strengthening Access to Justice through Legal Aid and Support Services - Lena Fischer; Thomas Weber; Anna Muller (Green Social: International Journal of Law and Civil Affairs, 2024)
Access to justice is fundamental to a fair legal system, yet many individuals face barriers due to financial constraints and limited resources. This article explores the role of legal aid and support services in enhancing access to justice, with a focus on vulnerable populations. The study evaluates the effectiveness of current legal aid programs, identifies key challenges, and suggests strategies for improving the availability and quality of legal assistance. The findings emphasize the importance of equitable legal support in ensuring justice for all.